Avaliação da influência de polimorfismos nos genes CYP3A5, PPARA e PORNA farmacocinética de tacrolimus, nefrotoxicidade e disfunção do enxerto em pacientes transplantados renais - EVERTON, Janaína Brito Freire (2019)
Chronic Kidney Disease consists of progressive and irreversible injury and loss of renal functions. The main treatment for patients with renal failure is transplantation, but a limitation of this therapy is the risk of graft rejection. The introduction of immunosuppressants was crucial for the functional maintenance of the transplanted organ. Tacrolimus (FK 506) is one of the major immunosuppressive agents used in clinical practice; however, it may cause nephrotoxicity and should therefore be administered at adjusted doses. Another factor to consider is the interindividual pharmacokinetic variability of immunosuppressants due to genetic polymorphisms. The present study aims to evaluate the influence of polymorphisms on CYP3A5 (rs776746), PPARA (rs4823613 and rs4253728) and POR (rs1057868) genes on tacrolimus pharmacokinetics in renal transplant patients in the first year after transplantation. Clinical and demographic data were collected from the medical records of patients treated at the HUUFMA Kidney Transplant Service. The determination of serum drug levels was performed by the chemiluminescence method. Polymorphisms were identified by real time PCR. The chi-square test (X2) was applied to assess the population's adherence to the Hardy-Weinberg equilibrium and the comparison between groups was made by the Mann-Whitne you test and the Kruskal-Wallis post hoc Dunn test. A total of 100 renal transplant patients were analyzed in the present study. An average age of 46.5 ± 14.1 years was observed and most of the sample was male (54%) and self-declared brown (82%). The most frequent alleles in the sample were allele *3 (69%), this being the variant allele for the CYP3A5 gene. For the other genes, wild type was the most prevalent; alleles A and G, corresponding to 64% and 82%, relative to the gene variant PPARA (rs4823613) and PPARA (rs4253728) genes, respectively; and for the POR gene the most frequent was the allele *1 (77%). The most prevalent genotypes in the sample were CYP3A5*1/*3 (36%) and CYP3A5*3/*3 (51%); PPARA (rs4823613) A/A (43%) and A/G (42%); PPARA (rs4253728) G/G (69%) and G/A (26%); POR *1/*1 (57%) and POR *1/*28 (38%). Homozygous patients for the non-functional CYP3A5 *3 allele had a higher adjusted concentration ratio (Co/D) (p <0.05) compared to those with at least one CYP3A5 *1 functional allele on tacrolimus pharmacokinetics. We did not observe a statistical relationship between Co/D and PPARA and POR genotype variants in the first year after transplantation, when analyzed as the only independent variable or when analyzed in expressers (*1/*1 and * 1/*3) and non-expressing (*3/*3) CYP3A5. Therefore, our results suggest that the polymorphism (rs776746) in the CYP3A5 gene plays a major role in tacrolimus pharmacokinetics whereas PPARA polymorphisms (rs4823613 and rs4253728) and POR appear not to be closely related to the interindividual variability observed in this drug metabolism. There was no association between polymorphisms and hepatic, renal and ethnicity function variables. In our understanding, the present study is the first study in Latin America to jointly evaluate the role of polymorphisms in the CYP3A5, PPARA, and POR genes (rs776746, rs4823613, rs4253728, and rs1057868) in tacrolimus pharmacokinetics in renal transplant patients.